Total Hip Arthroplasty: Anterolateral Approach Versus Posterior Approach - Azad Ahmad Ismael; Ali Abdalnabi Alwan Al-Tamimi (Advanced Medical Journal)
Background and objectives:Total hip arthroplasty is a popular successful surgical procedure for end stage hip pathologies. Since the introduction of total hip arthroplasty, many surgical approaches have been used; each has its own advantages and disadvantages. The aim of this study was to compare the intraoperative and post- operative complications of anterolateral (Watson-Jones) versus posterior (Moore) approaches for primary to-tal hip arthroplasty.